AMSTILATI ASSISTED PROJECT BASED LEARNING STRATEGY IMPLEMENTATION IN IMPROVING STUDENTS' READING COMPREHENSION - Muali, Chusnul; Rizqiah, Nurul Faroh (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This research was motivated by the low learning outcomes of Amsilati. Students who were still below standard. Based on this, the authors felt interested in conducting qualitative research to improve Amsilati learning outcomes by applying Project Based Learning strategies. This research is a descriptive study with a qualitative approach. The subjects in this study include educators, dormitory managers and students. Data collection techniques used were interviews, observation and documentation. The collected data is analyzed through several stages: display data, data reduction and conclusion. And the results of this study indicate that the Application of the Amtsilati Method in the Amsilati of Pondok Pesantren Islamiyah Syafi’iyah area able toimprove students’ reading comprehension of the book. The application of the Amsilati method is not in accordance with its application, it’s juts that there is a slight difference with the application of Amsilati at the center of the Darul Falah Islamic boarding school, Jepara. The learning process with the Amsilati method at the Islamiyah Syafi’iyah Islamic boarding school begins with reading khulashoh, hadloroh, qoidah then explanations, exposure to several examples, then evaluation.